P014 Giant Cell Arteritis Patient Pathway: A Multi-Disciplinary Approach to Service Improvement in the time of COVID-19. (23rd April 2022) - Mulhearn, Ben; Ellis, Jessica; Smith, Sarah; Tansley, Sarah L; Skeoch, Sarah
Abstract: Background/Aims: The RNHRD is a tertiary rheumatology centre offering a fast-track GCA assessment service. A 2018 departmental audit highlighted areas of good practice including timely assessment of cases but demonstrated irregularities in follow up processes. COVID-19 dramatically changed the way we could deliver our GCA service. Additionally, we saw increases in referrals, confirmed diagnoses and complex disease in our local population during the pandemic. This prompted us to undertake a service improvement project. Our main aims were to optimise follow up in line with national guidelines, enhance patient safety and improve the patient experience. Methods: We undertook a service review, starting by mapping the patients' journey. Guidelines were reviewed and stakeholders consulted. We identified several areas for improvement including; consultant-led risk stratification of patients, formalised follow up pathways and closer collaborative working with relevant departments. Additionally, we sought to streamline our processes to accommodate the increased COVID-19 workload. Results: A risk stratified follow up pathway was created. Patients are stratified at initial review, by consultants, into low and high-risk pathways. Follow up intervals have been standardised in line with BSR guidance. Follow up patients are reviewed in a dedicated clinic; medical and nursing clinics run supervised by a vasculitis specialist. Patients transfer between different clinics, dependent on clinical stability. Patient information provided has been standardised, with increased emphasis on flare management and steroid side effects. In collaboration with patients this is being incorporated into a "GCA patient passport", offering a consistent information resource for patients and clinicians. The nurse-led patient advice line is used frequently by GCA patients. All GCA queries are now directed to the on-call registrar, to ensure same day responses. Temporal artery ultrasound is well utilised and completed efficiently; 82% of scans between September 2019 and September 2021 occurred within 48 hours of referral. Via close working with vascular ultrasound, we have been able to create dedicated daily ultrasound capacity. Collaborative working with our Ophthalmology department has increased; communication channels between departments have been agreed, and education sessions have been provided. Processes for new GCA patients were streamlined, for example moving location of reviews. This ensured ongoing timely review of new GCA patients despite increased referral numbers. Conclusion: COVID-19 had a significant impact on service delivery but provided a catalyst to develop our service. By engaging with stakeholders across disciplines, and reacting to patient feedback, we have been able to institute effective and meaningful change. This process is iterative and we plan further assessment of outcomes including co-morbidities and complications. Further formal patient surveys and development of a GCA expert patient group are underway and will inform further service development. Disclosure: B. Mulhearn: None. J. Ellis: None. S. Smith: None. S.L. Tansley: None. S. Skeoch: None.